Comparing team accelerated instruction and jigsaw in mathematics: Effects on students’ learning interest and computational thinking skills - Darmaji Darmaji; Edy Widayat; Sucipto Sucipto (Rafandha Press, 2026)
Background: Enhancing students’ learning interest and computational thinking skills has become a critical objective of 21st-century education. Nevertheless, conventional instructional approaches often fail to optimally develop these competencies, necessitating the implementation of more effective cooperative learning models. Purpose: This study aims to compare the effects of the Team Accelerated Instruction (TAI) and Jigsaw learning models on students’ learning interest and computational thinking skills. Method: This study employed a quasi-experimental design using a non-equivalent control group design involving 56 tenth-grade students. Data were collected through a learning interest questionnaire and a computational thinking skills test. The data were analyzed using the Mann–Whitney U test with the assistance of SPSS version 25. Findings: The findings revealed that the Team Accelerated Instruction (TAI) model was more effective than the Jigsaw model in enhancing both students’ learning interest and computational thinking skills. The mean rank of computational thinking skills in the TAI group was 16.71, compared to 11.46 in the Jigsaw group, with a statistically significant difference (p < .05). Similarly, the mean rank of learning interest was higher in the TAI group (21.21) than in the Jigsaw group (15.25), and the difference was also statistically significant (p < .05). These findings indicate that the TAI model is more effective than the Jigsaw model in improving students’ learning interest and computational thinking skills.